Immersive Creativity: Redefining Artistic Expression in the Metaverse Era - Wei, Lie; Xiaoyu, Chen (International Journal of Art, Design, and Metaverse, 2025)
The emergence of the metaverse—a network of persistent, interconnected, and immersive virtual spaces—has begun to revolutionize artistic expression by transforming how art is conceived, produced, distributed, and experienced. Leveraging technologies such as virtual reality (VR), augmented reality (AR), and mixed reality (MR), the metaverse offers artists unprecedented opportunities to experiment with multidimensional forms, real-time collaboration, and interactive audience participation. This article examines how immersive technologies not only enhance creativity through sensory-rich and spatially dynamic environments but also democratize access by lowering geographical and institutional barriers to artistic engagement. By drawing on recent integrative reviews, global case studies, and established theoretical frameworks from media studies, art education, and digital culture, we identify the specific affordances—such as spatial immersion, avatar-mediated interaction, and programmable environments—that make virtual spaces conducive to novel forms of creativity. Furthermore, the study explores the sociocultural implications of this shift, including changes in authorship, intellectual property, and the role of curatorship in a decentralized art ecosystem. We conclude by discussing the potential trajectory of artistic practice in the metaverse, emphasizing the need for critical discourse on accessibility, ethical use, and sustainable technological integration in creative industries.